P-076 PROSPECTIVE COHORT STUDY ON MESH SHRINKAGE MEASURED WITH MRI AFTER ROBOT ASSISTED MINIMAL INVASIVE RETRORECTUS VENTRAL HERNIA REPAIR USING AN IRON OXIDE LOADED PVDF MESH. (13th October 2022) - Vierstraete, M; Beckers, R; Vangeel, L; Foriers, B; Pletinckx, P; Muysoms, F
Abstract: Aim: Mesh-reinforced ventral hernia repair is considered the gold standard treatment for all but the smallest of hernias. Human data on mesh shrinkage in the retrorectus mesh position is lacking. A prospective observational cohort study was performed to measure mesh shrinkage in robot assisted minimal invasive retrorectus repair of ventral hernias. Methods: A cohort of 20 patients underwent a robot assisted minimal invasive retrorectus repair of their ventral hernia. Magnetic resonance imaging (MRI) imaging was performed one month and thirteen months after implantation of an iron-oxide-impregnated polyvinylidene fluoride (PVDF) mesh to assess the decrease in mesh surface area. Inter-rater reliability among three radiologists regarding measurement of the mesh dimensions was analyzed. Quality of Life scoring was evaluated. Results: The inter-rater reliability between the radiologists reported as the intra-class correlations proved to be excellent for mesh width (ICC 0.95), length (ICC 0.98) and surface area (ICC 0.99). Between MRI measurements at one month and thirteen months postoperatively, there was a significant increase in mesh surface area (+12.0 cm 2, p=0.0013) and mesh width (+0.8 cm, p<0.001), while the length of the mesh remained unchanged (-0.1 cm, p=0.754). Quality of Life Scoring showed a significant improvement in Quality of Life after one month and a further improvement at thirteen months (p<0.001). Conclusion: There was an excellent inter-rater reliability between three radiologists when measuring width, length and surface area of an iron-oxide-impregnated PVDF mesh using MRI visualization. Mesh shrinkage was not observed, instead the effective mesh surface area and width of the mesh increased.